TV móvel no Brasil: análise do ambiente de negócios e fatores potenciais para o sucesso de serviços das operadoras de celular - Pinto, Marcelo Seabra (2008)
Mobile TV is growing in importance world wide and is of special interest for the mobile operators, which tries to get advantage through value added services in the current competitive environment. The goal of this dissertation is to find out what are the necessary factors for the mobile operators in Brazil to offer competitive TV services and to identify their weakness points. Moreover, new business opportunities within this area are searched for the mobile operators. The research utilizes the Technology Acceptance Model, of Davis and Bagozzi (1989), for a comprehension of the elements needed for the users to adopt new services of this nature. It s proposed to add a new construct for the classic model: the mass customization, taken from the model of Dynamic Stability, of Boyton, Victor and Pine (1993). A tactical analysis of the subject is also done, through the study of the value network of Mobile TV, supported by the theories of Porter (1986), Christensen and Rosenbloom (1995) and Kothandaraman and Wilson (2001). A field research was accomplished with 32 professionals of the four main Brazilian mobile operators to evaluate proposed elements in terms of importance and the quality level which are found in the market. In the same research, new business opportunities that could be interested for the mobile operators were analyzed. Additionally, the existing demand and the factors that could drive the Brazilian consumer to adopt the mobile TV were investigated through another field research with 272 mobile users, most of them young adults. The research produced results that can support Brazilian mobile operators on their investment decision in the promising area.